Learning Spring Batch avoiding the 3 AM batch processing trouble call - Minella, Michael T. (O'Reilly, 2016)
"Spring developers doing batch processing turn to Spring Batch for a multitude of reasons, but three stand out. First, Spring Batch is THE leading batch framework on the JVM. If you compare JSR 352 documentation (the Java spec for standardizing batch processing) with the documentation for Spring Batch, you'll see two virtually identical documents. For all intents and purposes, Spring Batch is JSR 352. Second, it can scale from a single JVM to multiple JVMs, which means it can handle any batch processing work load. Third, it has a compelling set of robust error handling capabilities that minimize errors and keeps (for the most part) your trouble pager from buzzing at 3 AM. Topics in this video include project setup, job configuration, reading and writing to various inputs and outputs, validating, processing, and filtering of data, as well as operational concerns such as error handling, receiving informational messages, and scaling jobs."--Resource description page.